Euphorbia myrsinites Sap-Induced Phytodermatitis: A Prototype of Irritant Contact Dermatitis?. Issue 2 (March 2019) - Weber, Benedikt; Sinz, Christoph; Bauer, Wolfgang M.; Kancz, Stefanie; Kittler, Harald; Kinaciyan, Tamar; Handisurya, Alessandra
Abstract : Background: A hallmark of Euphorbia myrsinites (EM), a member of the widespread perennial Euphorbia species, is the extrusion of a poisonous, latex-like sap irritant to the skin and eye after contact. The exact mechanisms underlying these effects have not been unraveled so far. Objectives: The aims of the study were to allocate EM sap–induced phytodermatitis to irritant or allergic contact dermatitis (ACD) and to investigate mechanism(s) causing keratinocyte damage. Methods: Cutaneous effects of EM sap on healthy human skin were investigated by clinical scoring and reflectance confocal microscopy analyses and compared with ACD. In addition, the effects of sap exposure to keratinocytes were analyzed in vitro using histological analyses and flow cytometry. Conclusions: We report on 2 cases of EM sap–induced phytodermatitis. Patch testing with fresh EM sap induced dermatitis in 100% of the tested sites with a clinical course following a decrescendo pattern. Compared with ACD, the lesional phenotype was more severe and epidermal disruption was more pronounced. Exposure of human skin tissues and cultivated keratinocytes to EM sap in vitro resulted in a dose-dependent increase in keratinocyte apoptosis. The reported findings support the primarily toxic irritant nature of EM sap–induced phytodermatitis. The contribution of ingenol mebutate to (nontoxic) proinflammatory effects remains to be elucidated. Abstract : Supplemental digital content is available in the text.